2020
DOI: 10.1158/0008-5472.can-19-2389
|View full text |Cite
|
Sign up to set email alerts
|

Risk SNP-Mediated Enhancer–Promoter Interaction Drives Colorectal Cancer through Both FADS2 and AP002754.2

Abstract: Although genome-wide association studies (GWAS) have identified more than 100 colorectal cancer risk loci, most of the biological mechanisms associated with these loci remain unclear.Here we first performed a comprehensive expression quantitative trait loci analysis in colorectal cancer tissues adjusted for multiple confounders to test the determinants of germline variants in established GWAS susceptibility loci on mRNA and long noncoding RNA (lncRNA) expression. Combining integrative functional genomic/epigen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…The effect of the already identified TFs with their binding sites affected by a nucleotide substitution on the expression of putative target genes is confirmed by siRNA-induced knockdown of the TFs [ 23 , 26 , 59 ] and/or their overexpression [ 16 , 20 , 26 , 74 ]. The same approaches are applied to detect widespread effects of rSNPs at the level of transcriptome [ 20 , 75 ].…”
Section: Modern Array Of Methods For Studying Individual Rsnpsmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect of the already identified TFs with their binding sites affected by a nucleotide substitution on the expression of putative target genes is confirmed by siRNA-induced knockdown of the TFs [ 23 , 26 , 59 ] and/or their overexpression [ 16 , 20 , 26 , 74 ]. The same approaches are applied to detect widespread effects of rSNPs at the level of transcriptome [ 20 , 75 ].…”
Section: Modern Array Of Methods For Studying Individual Rsnpsmentioning
confidence: 91%
“…Then the transcription levels of the selected genes are assayed [ 23 , 28 , 79 , 80 ] or a whole transcriptome analysis is performed [ 78 , 80 ]. A physical interaction between the region carrying an SNP and the potential target genes is usually confirmed with the help of Hi-C methods [ 26 , 28 , 59 , 80 ], including allele-specific chromosome conformation capture assays [ 74 ], or using available Hi-C data [ 59 , 79 , 81 ].…”
Section: Modern Array Of Methods For Studying Individual Rsnpsmentioning
confidence: 99%
“…[36][37][38][39][40] FADS3, as a fatty acid desaturase, was located along with FADS1 and FADS2, 41 which were reported to be associated with the occurrence and development of NSCLC and colon cancer. 42,43 Promoter methylation of RUBCNL was identified as a potential biomarker for early diagnosis of cervical cancer. 44 BIRC3, baculoviral IAP repeat-containing protein 3, as an apoptosis inhibitor, was overexpressed in multiple cancers and led to development of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PARP15, polymerase family member 15, was originally confirmed as a risk‐related gene in diffuse large B cell lymphomas, and might be potential predictors of hematological toxicity associated with RT for acute myeloid leukemia, cervical cancer, nasopharynx cancer, and tongue cancer 36–40 . FADS3, as a fatty acid desaturase, was located along with FADS1 and FADS2, 41 which were reported to be associated with the occurrence and development of NSCLC and colon cancer 42,43 . Promoter methylation of RUBCNL was identified as a potential biomarker for early diagnosis of cervical cancer 44 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs, which are polyadenylated, are larger than 200-nucleotide-long that are involved in gene expression [10][11][12]. Many studies have shown that long non-coding RNA was associated with the progression of various cancers [13][14][15][16]. Although lncRNAs in lung cancer are an emerging eld, HOTAIR, H19, ANRIL and MALAT1 have been shown to be involved in lung cancer [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%